STUDI RASIO KEUANGAN TERHADAP KINERJA BANK MUAMALAT INDONESIA - AH Suryansyah; Rusdiyanto Rusdiyanto (Universitas Islam Lamongan, 2016)
Further development of Islamic banking institutions in Indonesia to 1998 is still not fast because there is only one Islamic bank in operation. In 1998 issued Law no. 10 of 1998 to provide a stronger legal foundation for Islamic banking. Through law no. 23 of 1999, the government authorizes the Bank Indonesia to be able to carry out their duties based on Islamic principles. According to law no. 10 of 1998 and law no. 23 of 1999, the development of Islamic banking to rise sharply, especially from increasing the number of bank or office use Islamic principles and increasing the number of assets under management. The study population used in this study is the quarterly financial report of Bank Muamalat Indonesia in the period 2001 to 2010. Determination of sampling is a sampling technique in purposive sampling where the use of a subset of the population to represent the whole population, the data used in this study is secondary data, the data in the form of financial ratio of Bank Muamalat Indonesia processed quarterly financial statements of Bank Muamalat Indonesia in the period 2001 to 2010. R square value of 0.731, meaning 73.1 percent ROA is affected by the five independent variables CAR, NPF, FDR, BOPO and NIM. While the remaining 26.9 percent are influenced by other causes outside the model.Keywords : CAR, NPF, FDR, BOPO, NIM AND ROA